The last Acheuleans of south-eastern France.New overview of the Middle Pleistocene fauna of large mammals from Lazaret Cave (Nice, France) - Valensi, Patricia; Roussel, Audrey; Channarayapatna Visweswara, Sharada; Guennouni, Khalid El; Cauche, Dominique; Michel, Véronique (CCSD, 2022)
International audience Systematic excavations in Lazaret Cave over several decades (1967-2017), directed by Henry de Lumley, identified 29 levels of human occupation recording the cultural transition between the Acheulean and the Mousterian. Each level or archaeostratigraphic unit contained abundant archaeological and palaeontological material, sometimes associated with several human remains. The large mammal faunal spectrum includes 25 species and varies little from one unit to another. This faunal association and the evolutionary stages of certain species (Canis lupus, Ursus spelaeus, Cervus elaphus, Capra ibex) indicate that the archaeological deposits are correlated with the last Middle Pleistocene glacial period, MIS 6. On account of a specific geo-topography and moderate climatic impact, this region was a refuge zone for temperate species during glacial phases, resulting in the continuity of archaic species. The original faunal association of Lazaret Cave comprises temperate species with prevalent red deer (Cervus elaphus), ibex (Capra ibex) and aurochs (Bos primigenius). The antique elephant (Palaeoloxodon antiquus) also continued to live in the region during this cold phase. Relatively rare cold-climate mammals have been identified, such as the reindeer (Rangifer tarandus), the woolly rhinoceros (Coelodonta antiquitatis) and the wolverine (Gulo gulo). Archaeozoological analyses brought to light very diversified anthropic activities in the different archaeostratigraphic units. Here, we focus on the study of animal populations, combining classical methods to estimate the age and sex of slaughtered animals with cementochronological analyses. The results highlight and refine the seasonality of site occupations, and enhance our understanding of Acheulean subsistence and hunting strategies. In a regional context, these faunal data from Lazaret Cave broaden our knowledge of behavioural aspects of the Acheulean occupants of Lazaret Cave and their successors, Neanderthals from the Ligurian-Provencal zone. Les ...